PRODUCTION OF HIGGS IN TWO PHOTON COLLISION - Thi Ha Giang , Bui; Thi Le Thuy, Dao (HNUE Journal of Science: Journal of Natural Sciences, 2017)
The Higgs production was studied using the Randall-Sundrum model from photon-photon collision. The independent parameters in the Randall-Sundrum model: the vacuum expectation value of the radionfield \(Λ_φ\), the radion mass \(m_φ\), the Higgs mass \(m_h\) and ξ must be specified to fix the state mixing parameters. The total cross-section has been evaluated as the function of the parameters \(Λ_φ\), ξ, the collision energy \(s\) and the result shows the advantageous direction to observe the Higgs boson.